THE EFFECT OF PRINCIPALS' COMPETENCIES ON ACCREDITATION IN MADRASAH TSANAWIYAH THROUGHOUT TELLU SIATTINGE DISTRICT BONE REGENCY - Siti Aisyah; Muljono Damopolii; Sitti Mania (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract:This study described the effect of principals’ competencies on madrasah/school accreditation in Madrasah Tsanawiyah in Tellu Siattinge District in Bone Regency. Substitution of principals frequently occurred, having an impact on the achievement of accreditation. The principals’ competencies were managing and supervisory. Madrasah accreditation was the process of content standards, competency standards for graduates, standards for educators and educational staff, standards for facilities and infrastructure, financing standards, management standards, and procurement standards. Ex-post facto research was used to find the cause of an event. The population was 88 teachers, as well as the sample. The instrument was a questionnaire that was analyzed using descriptive statistics and inferential statistics by testing the hypothesis with the product-moment test and simple regression analysis.  The results showed that the reality of principals competencies with 86.56 of the average response rate was in the very good category with 66.9%. In the reality of madrasah accreditation, the average of respondents’ responses was 87.57, which was in the very good category with 68.2%. Furthermore, there was a positive and significant effect of principals' competencies on accreditation in Madrasah Tsanawiyah throughout Tellu Siattinge District in Bone Regency. The principals’ competencies of madrasah, which was utilized well by their leadership, provided an increase in madrasah accreditation. It was evidenced by 0.832 of the coefficient and 0.000 of the significance.Abstrak:Penelitian ini mendeskripsikan pengaruh kompetensi kepala madrasah terhadap akreditasi madrasah di Madrasah Tsanawiyah se-Kecamatan Tellu Siattinge Kabupaten Bone. Pergantian kepala madrasah sering terjadi, memberikan dampak terhadap pencapaian akreditasi madrasah. Kompetensi kepala madrasah di antaranya kompetensi manajerial dan kompetensi supervisi, sedangkan akreditasi madrasah dinilai melalui standar isi, standar proses, standar kompetensi lulusan, standar pendidik dan tenaga kependidikan, standar sarana dan prasarana, standar pembiayaan, standar pengelolaan serta standar penilaian. Penelitian ex-post facto digunakan dalam menemukan penyebab dari suatu peristiwa. Populasi penelitian adalah 88 guru sekaligus sebagai sampel. Teknik pengumpulan data dengan angket serta dianalisis dengan  statistik deksriptif dan statistik inferensial dengan pengujian hipotesis dengan uji korelasi product moment dan analisis regresi sederhana. Hasil penelitian menunjukkan bahwa Realitas kompetensi kepala madrasah dengan rata-rata tanggapan sebesar 86,56 berada pada kategori sangat baik dengan persentase sebesar 66,9%. Realitas akreditasi madrasah rata-rata tanggapan responden sebesar 87,57 berada pada kategori sangat baik dengan persentase sebesar 68,2%. Selanjutnya terdapat pengaruh yang positif dan signifikan kompetensi kepala madrasah terhadap akreditasi madrasah di Madrasah Tsanawiyah se-Kecamatan Tellu Siattinge Kabupaten Bone. Kompetensi kepala madrasah yang dimanfaatkan dengan baik oleh kepala madrasah dalam kepemimpinannya memberikan peningkatan terhadap pencapaian akreditasi madrasah, hal ini terbukti dengan koefisien 0,832 dan siginifikansi 0,000.